Answer:
See the procedure.
The solution is:
Explanation:
In order to solve the system using the Substitution method, you can follow these steps:
1. Substitute the second equation
and the third equation
into the first equation
; and then solve for "B":
![(5B )+3B-2(2B-2)=20\\\\8B-4B+4=20\\\\4B=20-4\\\\B=(16)/(4)\\\\B=4](https://img.qammunity.org/2020/formulas/mathematics/high-school/ext87z8jdapze1ipj5v4k6lfgivelv9uju.png)
2. Knowing the value of "B", substitute it into the the second equation to find "A":
![A=5(4)\\\\A=20](https://img.qammunity.org/2020/formulas/mathematics/high-school/qq1b3ulxbor5zxqo039514z3dle1ud86us.png)
3. Substitute the value of "B" into the third equatio to find "C":